IMPLEMENTASI PEMBELAJARAN BAHASA ARAB DENGAN PROJECT BASED LEARNING DI MA'HAD SA'AD BIN ABI WAQQASH PALEMBANG - Nurul hasanah; ni putri asyura; Yuniar; nazarmanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the implementation of the Project-Based Learning(PjBL) method in Arabic language learning at the secondary school level. Thisqualitative research uses a case study approach involving several teachers andstudents who apply PjBL in Arabic language classes. Data were collected throughin-depth interviews with teachers, classroom observations, and analysis ofstudents project documents. The findings of the study indicate that theimplementation of PjBL has a positive impact on improving students speaking,writing, and cultural understanding skills in Arabic. In addition, students becomemore active, creative, and engaged in the learning process. However, thechallenges faced include time and resource limitations, as well as the need forteacher training to effectively implement this method. This study suggests thatPjBL should be more widely applied in Arabic language learning, with moreintensive training support for teachers.